Eksistensi OJK Pada Lembaga Keuangan di Indonesia - Dwi Anindya Harimurti (Lembaga Pengembangan Kinerja Dosen, 2024)
This study uses a normative juridical method with the aim of conducting an analysis of the roles and functions attached to the Financial Services Authority (OJK) in accordance with statutory regulations as the basis for its formation. Based on the research that has been conducted, the results show that OJK has the duty and authority to regulate and supervise financial service activities in the banking, capital market, insurance, pension funds, financing institutions, and other financial services sectors. Referring to the authority contained in the OJK, its roles and functions include regulating and supervising financial institutions both in the category of banks and non-bank financial institutions.